2022
DOI: 10.3389/fendo.2022.826665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Paternal Obesity on Fetal Development and Pregnancy Complications: A Prospective Clinical Cohort Study

Abstract: ObjectivesTo evaluate the association between paternal obesity and fetal development and pregnancy complications.Study DesignThis prospective cohort clinical trial analyzed data from 7683 women with singleton pregnancies. All study subjects were sequentially divided into four groups based on paternal BMI. We compared the differences in fetal growth and pregnancy complications between different paternal BMI groups by univariate logistic regression and independent t-test. Finally, the independent predictors of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 79 publications
3
17
0
Order By: Relevance
“…In this study, we found that paternal obesity before pregnancy was significantly related to an increased risk of macrosomia in babies and pregnancy complications in mothers, including HDCP, cesarean delivery, and GWG over guidelines. It is similar to the results of Lin J et al (28). Moreover, the incidences of SGA in offspring were significantly higher in the underweight paternal groups.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, we found that paternal obesity before pregnancy was significantly related to an increased risk of macrosomia in babies and pregnancy complications in mothers, including HDCP, cesarean delivery, and GWG over guidelines. It is similar to the results of Lin J et al (28). Moreover, the incidences of SGA in offspring were significantly higher in the underweight paternal groups.…”
Section: Discussionsupporting
confidence: 91%
“…Placentas derived from obese sires, like hypoxic placentas, exhibit changes in gene expression and altered angiogenesis, vasculature, and development (Binder et al, 2015, 2012; Jazwiec et al, 2022; Lin et al, 2022; McPherson et al, 2015; Mitchell et al, 2017). Hypoxia is a tightly regulated process during placental development which is essential for proper vascular formation.…”
Section: Resultsmentioning
confidence: 99%
“…In human studies, recurrent pregnancy loss is associated with increased seminal reactive oxygen species (ROS) and sperm DNA damage (Jayasena et al, 2019). Male partner metabolic syndrome and being overweight have been associated with an increased risk for pre-eclampsia and negative pregnancy outcomes (Lin, Gu, & Huang, 2022; Murugappan et al, 2021). Animal models suggest that pregnancy complications that have been associated with paternal metabolic complications may be a consequence of placental dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this recommendation, almost 50% of women who were preparing for pregnancy were not taking folic acid, indicating a lack of understanding of the importance of preconception folic acid. Additionally, one of the main reasons given for why partners were not preparing was "We didn't know that they should be doing anything" suggesting that people are unaware of the impact that preconception paternal health can have (4,10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Almost 50% of women in the UK are either overweight (BMI >25 kg/m 2) or obese (BMI >30 kg/m 2 ) when they become pregnant (1,6) which is associated with substantial risks for both mother and child, including sub-fertility, pregnancy complications, congenital fetal malformations and stillbirth (1,(7)(8)(9). However, it is not just maternal obesity that is an issue; paternal obesity has also been linked to impaired fertility, increased risk of adverse pregnancy outcomes and chronic disease risk in offspring (1,10,11). Despite the prevalence of overweight and obesity, micronutrient deficiencies continue to be a growing issue globally; studies have shown that many women of reproductive age will have dietary intakes below the recommend reference nutrient intake (RNI) for many micronutrients (1).…”
Section: Introductionmentioning
confidence: 99%